Extrapolation of Adult Efficacy to Pediatric Patients With Chemotherapy‐Induced Nausea and Vomiting. (22nd January 2020) - Momper, Jeremiah D.; Heinrichs, M. Tobias; Krudys, Kevin; Griebel, Donna; Kumar, Shaun; Kim, Insook; Mehrotra, Nitin; Mulberg, Andrew E.; Garimella, Narayana; Nelson, Robert; Reaman, Gregory; Sinha, Vikram; et al.
Abstract: Chemotherapy‐induced nausea and vomiting (CINV) is a common treatment‐related adverse event that negatively impacts the quality of life of cancer patients. During pediatric drug development, extrapolation of efficacy from adult to pediatric populations is a pathway that can minimize the exposure of children to unnecessary clinical trials, improve efficiency, and increase the likelihood of success in obtaining a pediatric indication. The acceptability of the use of extrapolation depends on a series of evidence‐based assumptions regarding the similarity of disease, response to intervention, and exposure‐response relationships between adult and pediatric patients. This study evaluated publicly available summaries of data submitted to the US Food and Drug Administration for drugs approved for CINV to assess the feasibility of extrapolation for future development programs. Extracted data included trial design, emetogenic potential of chemotherapy, primary end points, participant enrollment criteria, and antiemetic pharmacokinetics. Adult and pediatric clinical trial designs for assessment of efficacy and safety shared key design elements. Antiemetic drugs found to be efficacious in adults were also efficacious in pediatric patients. Systemic drug concentrations at approved doses were similar for ondansetron, granisetron, and aprepitant, but an exposure‐response analysis of palonosetron in children suggested that higher palonosetron systemic exposure is necessary for the prevention of CINV in the pediatric population. For 5‐hydroxytryptamine‐3 and neurokinin‐1 receptor antagonist antiemetic drugs, efficacy in adults predicts efficacy in children, supporting the extrapolation of effectiveness of an antiemetic product in children from adequate and well‐controlled studies in adult patients with CINV.